Evaluation of ceramic flexural strength of a cobalt-chromium alloy subjected to airborne particle abrasion and tungsten inert gas welding - Laise Pena Braga Monteiro; Issae Sousa Sano; Suelen Reis Cunha; Eliza Burlamaqui Klautau; Bruno Pereira Alves (Universidade Estadual de Campinas, 2019)
Aim: The aim of this study was to evaluate the influence of tungsten inert gas (TIG) welding and airborne particle abrasion using aluminum oxide particles on the flexural strength of a joint between ceramic and cobalt-chromium alloys. Methods: The specimens were cast and welded using TIG, then divided into 6 groups (n = 10) and subjected to blasting with 250 μm, 100 μm, and 50 μm aluminum oxide particles. Ceramic systems were applied to the central part of all specimens. A three-point bending test using a velocity of 0.5 mm/m was performed on the specimens to measure flexural strength. Data were analyzed using two-way analysis of variance and Tukey's test. Results: TIG welding demonstrated the lowest resistance compared with the non-welded groups. Airborne particle abrasion using 250 μm aluminum oxide particles demonstrated greater resistance in the welded groups (p < 0.05). Mixed faults were found in all specimens. Conclusion: TIG welding decreased the bond strength, and the particle size of aluminum oxide did not affect the metal-ceramic bond in groups without TIG welding.